Application of Phytochemical and Elemental Profiling, Chemometric Multivariate Analyses, and Biological Activities for Characterization and Discrimination of Fruits of Four Garcinia Species. (2nd January 2020) - Jamila, Nargis; Khan, Naeem; Hwang, In Min; Nho, Eun Yeong; Choi, Ji Yeon; Atlas, Amir; Khan, Sadiq Noor; Amin, Farhat; Javed, Fatima; Kim, Kyong Su
Abstract: Species of Garcinia (Guttiferae) are used for flavoring curries, as a supplement, and to treat various diseases. This study describes the comparison and discrimination of Garcinia cambogia, Garcinia indica, Garcinia mangostana and Garcinia atroviridis fruits by analyzing their major phytochemicals, elemental content, antioxidant, antidiabetic, and anticholinesterase enzymes activities. For phytochemical and elemental profiling, ultraviolet (UV), near infrared/infrared (NIR/IR), inductively coupled plasma-optical emission spectroscopy (ICP-OES) and ICP-mass spectrometric (ICP-MS) techniques were used. The chemometric multivariate tests of linear discriminant and principal component analyses (LDA, PCA) were used to discriminate the subject fruit samples. Spectroscopic data showed resonances of phenolics and flavonoidal constituents present in the fruits. G. mangostana exhibited the highest phenolics (721.6 to 2815.3 µM GAE/g), whereas G. cambogia was rich in flavonoids (51.9 to 2709.2 µM QE/g). Anthocyanin (cyanidin-3- O -glucoside) evaluated by high performance liquid chromatographic was 9.01 mg/kg in G. mangostana fruit. In the analyzed fruits, Ca, K and Na were high, trace essential elements were at appreciable contents, whereas the toxic elements As, Cd, Tl, and Pb were within the safe limits. G. mangostana contained potent free radicals and cholinesterase enzyme inhibitors, whereas G. cambogia inhibited α -amylase enzyme more significantly. PCA and LDA discriminated the fruit samples with distinct classification and variability indices. The analyzed fruits were shown to be good sources of free radicals, cholinesterase, and α-amylase enzymes inhibition, mineral and essential elements, and safe for human consumption.